Association between corpus callosum development on magnetic resonance imaging and diffusion tensor imaging, and neurodevelopmental outcome in neonates born very preterm. (14th December 2016) - Malavolti, Anna M; Chau, Vann; Brown‐Lum, Meisan; Poskitt, Kenneth J; Brant, Rollin; Synnes, Anne; Grunau, Ruth E; Miller, Steven P
Abstract : Aim: To characterize corpus callosum development in neonates born very preterm from early in life to term‐equivalent age and its relationship with neurodevelopmental outcome at 18 months corrected age. Method: In a prospective cohort of 193 neonates born preterm, 24 to 32 weeks' gestation, we used magnetic resonance imaging and diffusion tensor imaging acquired early in life ( n =193) and at term‐equivalent age ( n =159) to measure corpus callosum development: mid‐sagittal area (including corpus callosum subdivisions) and length, and fractional anisotropy from the genu and splenium. We examined the association of (1) intraventricular haemorrhage (IVH) and white matter injury (WMI) severity, and (2) neurodevelopmental outcome at 18 months corrected age with corpus callosum development. Results: Severe WMI and severe IVH were strongly associated with reduced corpus callosum area (both p <0.001) and WMI with lower fractional anisotropy ( p =0.002). Mild WMI predicted smaller corpus callosum area only posteriorly; mild IVH predicted smaller area throughout. Adverse motor outcome was associated with smaller corpus callosum size in the posterior subdivision ( p =0.003). Abnormal cognitive outcomes were associated with lower corpus callosum fractional anisotropy ( p =0.008). Interpretation: In newborn infants born very preterm, brain injury is associated with changes in simple metrics of corpus callosum development. In this population, the development of the corpus callosum, as reflected by size and microstructure, is associated with neurodevelopmental outcomes at 18 months corrected age. What this paper adds: Corpus callosum development reflects the severity of white matter injury and intraventricular haemorrhage. Corpus callosum development reflects brain development and is associated with motor outcome at 18 months of age. Normative values for corpus callosum size are provided through term‐equivalent age in neonates born at 24 to 32 weeks' gestation. This article is commented on by Steinweg and Arichi on pages351–352 of this issue. Video Podcast:https://youtu.be/70mRYy7cKOk